The probability of economic success in exploring for tin deposits - Victor Rudenno (Canadian Institute of Mining, Metallurgy and Petroleum, 1981)
"Previous methods have employed statistical analysis to model future mineral resources. The method presented in this paper uses Zipj's Law to determine the size and grade of tin deposits still to be discovered. The law is applied independently to both known deposit tonnage and grades. A probability distribution for both 'tonnage and grade is computed/or those deposits still to be located and then, by applying a correlation between tonnage and grade, a distribution of the probability of metal content discovery is obtained.By considering an economic cut-off in metal contained in a deposit, the probability of economic success for the next tin discovery is computed, both for a world discovery and for the special case of Tasmania, Australia. The results indicate a probability of 11-37% on a world-wide basis and 18% chance of economic success in Tasmania.IntroductionIn the past , most attempts to determine the probability of success in finding an economic mineral deposit have relied on the accumulation of statistical data. These data are then used to predict a suitable frequency distribution to assess the probability of finding a deposit of a given size and grade (Singer,1975).The method not only relies on one having sufficient data, but also on the assumption that the data are not biased and that the distribution (usually log-normal) is a correct one. The method presented in this paper, to analyze tin deposits, uses Zipf's Law, which has been recently applied to oil, uranium, lead-zinc and gold deposits by Folinsbee (1977) and to Western Australian gold deposits by Rowlands and Sampey (1977). Tapp and Koniuszko (1978) have applied Zipf's Law to mineral distribution patterns in the Northern Australian orogenic provinces, which has enabled them to make predictions with a relatively small data source."